2013
DOI: 10.1016/j.jcf.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the inflammatory regulator A20 correlates with lung function in patients with cystic fibrosis

Abstract: A20 expression is reduced in CF and is proportional to FEV1. Pending confirmation in a larger study, A20 may prove a novel predictor of CF inflammation/disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…antibiotics, but augmented CFTR function failed to reduce inflammatory markers in sputum (e.g., IL-1, -6, -8) (26), and heterogeneous responses to the treatment have been reported (27), suggesting that CFTR correction/potentiation may not directly improve the underlying compromised immune response. The negative NF-κB regulator A20 (TNFAIP3) is reduced in CF airway epithelial cells, basally and after LPS stimulation (23), and is associated with markers of inflammation and decreased lung function (12). A20 silencing increased TRAF6 and NF-κB activity (18), and A20 overexpression had protective effects in airway inflammation in asthmatic mice (28), suggesting that A20 augmentation normalizes the inflammatory response in the airways.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…antibiotics, but augmented CFTR function failed to reduce inflammatory markers in sputum (e.g., IL-1, -6, -8) (26), and heterogeneous responses to the treatment have been reported (27), suggesting that CFTR correction/potentiation may not directly improve the underlying compromised immune response. The negative NF-κB regulator A20 (TNFAIP3) is reduced in CF airway epithelial cells, basally and after LPS stimulation (23), and is associated with markers of inflammation and decreased lung function (12). A20 silencing increased TRAF6 and NF-κB activity (18), and A20 overexpression had protective effects in airway inflammation in asthmatic mice (28), suggesting that A20 augmentation normalizes the inflammatory response in the airways.…”
Section: Discussionmentioning
confidence: 99%
“…A common feature of CF is the heightened, chronic inflammatory response to Pseudomonas aeruginosa, driven by constitutive NF-κB activation in airway and peripheral blood cells (2,3,11). Primary nasal epithelial cells (PNECs) from patients with the common Phe508del/Phe508del mutation and a milder genotype (R117H/ Phe508del) show a significant increase in NF-κB(p65), which correlates with disease severity (12). A20 [TNFα-induced protein 3 (TNFAIP3)] is a central negative regulator of NF-κB activation following stimulation of TLRs and/or TNF receptor and regulates different signaling pathways such as NF-κB and IFN regulatory factor signaling (13).…”
Section: Cf Airway Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhanced A20 mRNA expression occurs following infection of mice with P. aeruginosa [22] We have previously shown that the prolonged NF-κB driven inflammatory response in CF airway epithelial cells is associated with reduced expression of A20 [23] and most importantly this lack of A20 correlates with reduced lung function in patients with CF [24]. Onose et al described virus induced induction of A20 in human bronchial epithelial cell lines and mouse lung homogenates.…”
Section: A20 In the Airwaysmentioning
confidence: 99%